Regulating international clinical research: an ethical framework for policy-makers. Issue 5 (26th May 2020) - Aguilera, Bernardo; DeGrazia, David; Rid, Annette
Abstract : The global distribution of clinical trials is shifting to low-income and middle-income countries (LMICs), and adequate regulations are essential for protecting the rights and interests of research participants in these countries. However, policy-makers in LMICs can face an ethical trade-off: stringent regulatory protections for participants can lead researchers or sponsors to conduct their research elsewhere, potentially depriving the local population of the opportunity to benefit from international clinical research. In this paper, we propose a three-step ethical framework that helps policy-makers to navigate this trade-off. We use a recent set of regulatory protections in Chile to illustrate the practical value of our proposed framework, providing original ethical analysis and previously unpublished data from Chile obtained through freedom of information requests.